Cross-cultural Communication Barrier at Southeast Sulawesi - Aldilal (International Journal of Global Community, 2020)
The purpose of this research is to find out obstacles of cross-cultural communication between Chinese workers and local workers at PT. Virtue Dragon Nickel Industrial in Sulawesi Tenggara Indonesia. This study methodology uses a qualitative descriptive approach to describing social phenomena. The study depicts the social reality in which the author performs directly in the field. Samples of this study were taken by the snowball sampling method. Findings showed that cross-cultural communication barriers between Chinese workers and local workers at PT. Virtue Naga Nickel industry in southeast Sulawesi are differences in language, Nonverbal Communication, the group’s likelihood and cultural differences. This paper contributes to the literacy of foreign workers and local workers in Indonesia and for the development of Science in communication sciences, especially intercultural communication.